Peningkatan Kemampuan Operasi Hitung Siswa Kelas VII Melalui Program Kelas Numerasi SMPN 16 Mataram - Aini, Nurzilatul; S. Antya Rohmawati; Tri Saputri (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Numeracy skills are fundamental abilities that every student must possess to understand mathematical concepts. Indonesia ranks 74th out of 79 countries in terms of numeracy proficiency, indicating the low ability of students to comprehend basic mathematical concepts and solve numeracy-based problems. According to the 2024 National Assessment results, the majority of students in this region fall into the low category for numeracy literacy. This is further supported by data from SMPN 16 Mataram, where field observations reveal that many students struggle with mastering basic arithmetic operations such as addition, subtraction, multiplication, and division, which are foundational for understanding more advanced mathematical concepts. Therefore, this community service aims to help students develop skills in understanding and operating basic algebraic concepts, such as addition, subtraction, multiplication, and division of algebraic expressions. This service is conducted at SMPN 16 Mataram, located in Mataram city, with the participants being 23 students from class VII of SMP in Mataram. The data used in this service activity is sourced from the implementation of the Madrasah Indonesia Competency Assessment (AKM) guidance activity to improve students' literacy and numeracy competencies at SMPN 16 Mataram, conducted by 7th grade mathematics teacher. The evaluation of the activity was done through interviews with both the teacher and the students of grade 7th. The results of this activity show a significant improvement in the numeracy skills of students in algebraic arithmetic operations at SMPN 16 Mataram, class VII. This improvement is measurable, with the average score initially at 40, which then increased to 70 after the implementation of the program or community service activities. This indicates that students who previously had difficulty understanding and mastering algebraic arithmetic operations, such as addition, subtraction, multiplication, and division with variables or algebraic expressions, made significant progress after being given guidance and practice. Therefore, the addition of numeracy-focused programs is effective in helping students solve problems.